Fabrication of Silk Fibroin/P(LLA‐CL) Aligned Nanofibrous Scaffolds for Nerve Tissue Engineering. Issue 5 (22nd October 2012) - Zhang, Kuihua; Jinglei, Wu; Huang, Chen; Mo, Xiumei; Kim, Il‐Doo
Abstract Aligned nanofibers are an attractive option in neural tissue engineering due to providing topographic cues for cell and axonal growth. Aligned and radom 25:75 wt% silk fibroin/poly[(L‐lactic acid)‐co‐(ε‐caprolactone)] nanofibrous scaffolds are fabricated via electrospinning. The mechanical properties of aligned scaffolds present a strong anisotropy, with much higher tensile strength in parallel than in perpendicular direction. Schwann cell viability studies show that aligned scaffolds significantly promote cell growth and the direction of SC elongation is parallel to the direction of fibers for aligned scaffolds. These results suggest that aligned nanofibrous scaffolds might be potential candidates for nerve tissue engineering. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>